2017
DOI: 10.3390/nu9091036
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Eicosapentaenoic Acid Inversely Relates to MRI-Assessed Carotid Plaque Lipid Core Burden in Elders at High Cardiovascular Risk

Abstract: Supplemental marine omega-3 eicosapentaenoic acid (EPA) has an anti-atherosclerotic effect. Clinical research on EPA supplied by the regular diet and atherosclerosis is scarce. In the framework of the PREvención con DIeta MEDiterránea (PREDIMED) trial, we conducted a cross-sectional study in 161 older individuals at high vascular risk grouped into different stages of carotid atherosclerosis severity, including those without ultrasound-detected atheroma plaque (n = 38), with plaques <2.0 mm thick (n = 65), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
2
0
2
Order By: Relevance
“…Em relação aos AGPIs n-3, as evidências clínicas recentes de DCV são mais consistentes. Estudos observacionais com AGPI n-3 de hemácias 18 , 36 - 40 e ensaios clínicos randomizados 41 - 43 mostraram que o AGPI n-3 reduz o risco de DCV. Nossos resultados corroboram o efeito cardioprotetor dos AGPIs n-3, mas mostram forte influência do ALA devido à baixa ingestão de EPA e DHA (Tabela Complementar 1).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Em relação aos AGPIs n-3, as evidências clínicas recentes de DCV são mais consistentes. Estudos observacionais com AGPI n-3 de hemácias 18 , 36 - 40 e ensaios clínicos randomizados 41 - 43 mostraram que o AGPI n-3 reduz o risco de DCV. Nossos resultados corroboram o efeito cardioprotetor dos AGPIs n-3, mas mostram forte influência do ALA devido à baixa ingestão de EPA e DHA (Tabela Complementar 1).…”
Section: Discussionunclassified
“…Concerning n-3 PUFA, the recent clinical evidence for CVD is more consistent. Observational studies with RBC n-3 PUFA 18 , 36 - 40 and randomized clinical trials 41 - 43 showed that n-3 PUFA reduce CVD risk. Our results corroborate with the cardioprotective effect of n-3 PUFA but showed a strong influence of ALA due to the low EPA and DHA intake (Supplementary Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, a study evaluating individuals with acute coronary syndrome found that for a 1 unit increase in the w3 index, the odds ratio for the disease decreased by 23% . Other studies have shown that an EPA concentration alone that is higher than 1% is associated with greater atherosclerotic plaque stabilization in carotids and a better lipid profile in high cardiovascular risk elderly patients, as well as a reduction in mortality independent of other risk factors . Recently, the omega‐3 index was associated with lower risks for total mortality, non‐CVD and noncancer mortality, and total CVD events in the Framingham Heart Study Offspring cohort.…”
Section: Discussionmentioning
confidence: 99%